Accelerating Oxygen-Reduction Catalysts through Preventing Poisoning with Non-Reactive Species by Using Hydrophobic Ionic Liquids - Zhang, Guirong; Munoz, Macarena; Etzold, Bastian (Angewandte Chemie International Edition, 2016)
Developing cost-effective electrocatalysts for the oxygen reduction reaction (ORR) is a prerequisite for broad market penetration of low-temperature fuel cells. A major barrier stems from the poisoning of surface sites by nonreactive oxygenated species and the sluggish ORR kinetics on the Pt catalysts. Herein we report a facile approach to accelerating ORR kinetics by using a hydrophobic ionic liquid (IL), which protects Pt sites from surface oxidation, making the IL-modified Pt intrinsically more active than its unmodified counterpart. The mass activity of the catalyst is increased by three times to 1.01 A mg-1Pt@0.9 V, representing a new record for pure Pt catalysts. The enhanced performance of the IL-modified catalyst can be stabilized after 30 000 cycles. We anticipate these results will form the basis for an unprecedented perspective in the development of high-performing electrocatalysts for fuel-cell applications.
EAM Import::2019-03-13

Boosting performance of low temperature fuel cell catalysts by subtle ionic liquid modification - Zhang, Guirong; Munoz Garcia, Macarena; Etzold, Bastian (ACS Applied Materials and Interfaces, 2015)
High cost and poor stability of the oxygen reduction reaction (ORR) electrocatalysts are the major barriers for broad-based application of polymer electrolyte membrane fuel cells. Here we report a facile and scalable approach to improve Pt/C catalysts for ORR, by modification with small amounts of hydrophobic ionic liquid (IL). The ORR performance of these IL-modified catalysts can be readily manipulated by varying the degree of IL filling, leading to a 3.4 times increase in activity. Besides, the IL-modified catalysts exhibit substantially enhanced stability relative to Pt/C. The enhanced performance is attributed to the optimized microenvironment at the interface of Pt and electrolyte, where advantages stemming from an increased number of free sites, higher oxygen concentration in the IL and electrostatic stabilization of the nanoparticles develop fully, at the same time that the drawback of mass transfer limitation remains suppressed. These findings open a new avenue for catalyst optimization for next-generation fuel cells.
EAM Import::2019-03-13

Carbide-derived carbon with hollow core structure and its performance as catalyst support for methanol electro-oxidation - Ariyanto, Teguh; Kern, Andreas; Etzold, Bastian; Zhang, Guirong (Electrochemistry Communications, 2017)
New hollow core particles of mesoporous/graphitic carbon were successfully prepared from carbon core-shell particles, through selective removal of the core. Electrocatalysts prepared by dispersing platinum on these hollow core materials showed remarkably high dispersion. The combination of high dispersion with short pore diffusion length allowed to obtain high mass specific activity in methanol electro-oxidation (ca. 390 A gPt − 1), along with excellent long-term stability. These novel carbon nanostructures show great promise as Pt catalyst support for methanol oxidation.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; Fuel cells; Hollow core particles; Methanol electro-oxidation; Pt electrocatalysts

Controlled synthesis of core-shell carbide-derived carbons through in situ generated chlorine - Ariyanto, Teguh; Zhang, Guirong; Riyahi, Farshad; Gläsel, Jan; Etzold, Bastian (Carbon, 2017)
Core-shell porous carbon represents an innovative concept for optimizing performances of carbon materials in a wide range application. Here, a novel route to produce carbons with spatially varying pore and microstructure is presented. Following the carbide-derived carbon method, a homogeneous and adjustable shell generation is achieved through mixing a limited amount of solid chlorine precursors with titanium carbide raw material. Chlorine is released in situ when reaching approx. 600 °C and consumed subsequently directly, resulting in the aspired materials. Various characterization methods proved that the amount of solid chlorine precursor directly adjusts the share of the shell for the core-shell material, while a range of 5–80% was studied. The amorphous, microporous shell can be converted to a mesoporous and graphitic shell (crystal sizes 20 nm), through a subsequent vacuum annealing, allowing to control the properties of the carbon shell. The carbon core results after a subsequent second chlorination step, where directly gaseous chlorine is used. The materials were characterized in detail after every step of this novel route. Adjusting the share between mesoporous/graphitic shell and microporous/amorphous core for these new materials is of interest in applications where competing processes like mass transfer and surface interaction need to be optimized.
CRIS-Team Scopus Importer:2023-08-15

Improving control of carbide-derived carbon microstructure by immobilization of a transition-metal catalyst within the shell of carbide/carbon core shell structures - Ariyanto, Teguh; Gläsel, Jan; Kern, Andreas; Zhang, Guirong; Etzold, Bastian (Beilstein Journal of Nanotechnology, 2019)
Carbon materials for electrical energy devices, such as battery electrodes or fuel-cell catalysts, require the combination of the contradicting properties of graphitic microstructure and porosity. The usage of graphitization catalysts during the synthesis of carbide-derived carbon materials results in materials that combine the required properties, but controlling the microstructure during synthesis remains a challenge. In this work, the controllability of the synthesis route is enhanced by immobilizing the transition-metal graphitization catalyst on a porous carbon shell covering the carbide precursor prior to conversion of the carbide core to carbon. The catalyst loading was varied and the influence on the final material properties was characterized by using physisorption analysis with nitrogen as well as carbon dioxide, X-ray diffraction, temperature-programmed oxidation (TPO), Raman spectroscopy, SEM and TEM. The results showed that this improved route allows one to greatly vary the crystallinity and pore structure of the resulting carbide-derived carbon materials. In this sense, the content of graphitic carbon could be varied from 10-90 wt % as estimated from TPO measurements and resulting in a specific surface area ranging from 1500 to 300 m(2)g(-1).
CRIS-Team WoS Importer:2019-02-21

Ionic liquids in electrocatalysis - Zhang, Guirong; Etzold, Bastian (Journal of Energy Chemistry, 2016)
The performance of an electrocatalyst, which is needed e.g. for key energy conversion reactions such as hydrogen evolution, oxygen reduction or CO2 reduction, is determined not only by the inherent structure of active sites but also by the properties of the interfacial structures at catalytic surfaces. Ionic liquids (ILs), as a unique class of metal salts with melting point below 100 °C, present themselves as ideal modulators for manipulations of the interfacial structures. Due to their excellent properties such as good chemical stability, high ionic conductivity, wide electrochemical windows and tunable solvent properties the performance of electrocatalysts can be substantially improved through ILs. In the current minireview, we highlight the critical role of the IL phase at the microenvironments created by the IL, the liquid electrolyte, catalytic nanoparticles and/or support materials, by detailing the promotional effect of IL in electrocatalysis as reaction media, binders, and surface modifiers. Updated exemplary applications of IL in electrocatalysis are given and moreover, the latest developments of IL modified electrocatalysts following the ``Solid Catalyst with Ionic Liquid Layer (SCILL)'' concept are presented.
EAM Import::2019-03-12

Preparation of hollow mesoporous carbon spheres and their performances for electrochemical applications - Ariyanto, T.; Zhang, Guirong; Kern, Andreas; Etzold, Bastian (IOP Conference Series: Materials Science and Engineering, 2018)
Hollow carbon materials have received intensive attention for energy storage/conversion applications due to their attractive properties of high conductivity, high surface area, large void and short diffusion pathway. In this work, a novel hollow mesoporous material based on carbide-derived carbon (CDC) is presented. CDC is a new class of carbon material synthesized by the selective extraction of metals from metal carbides. With a two-stage extraction procedure of carbides with chlorine, firstly hybrid core-shell carbon particles were synthesized, i.e. mesoporous/graphitic carbon shells covering microporous/amorphous carbon cores. The amorphous cores were then selectively removed from particles by a careful oxidative treatment utilizing its low thermal characters while the more stable carbon shells remained, thus resulting hollow particles. The characterization methods (e.g. N2 sorption, Raman spectroscopy, temperature-programmed oxidation and SEM) proved the successful synthesis of the aspired material. In electric double-layer capacitor (EDLC) testing, this novel hollow core material showed a remarkable enhancement of EDLC's rate handling ability (75% at a high scan rate) with respect to an entirely solid-mesoporous material. Furthermore, as a fuel cell catalyst support the material showed higher Pt mass activity (a factor of 1.8) compared to a conventional carbon support for methanol oxidation without noticeably decreasing activity in a long-term testing. Therefore, this carbon nanostructure shows great promises as efficient electrode materials for energy storage and conversion systems.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; Electric-double layer capacitors; Hollow carbon spheres; Methanol oxidation

Producing high quality carbide-derived carbon from low quality byproducts stemming from SiC production - Ariyanto, Teguh; Mohd Laziz, Afiq; Gläsel, Jan; Zhang, Guirong; Garbes, Josef; Etzold, Bastian (Chemical Engineering Journal, 2016)
The utilization of carbide-derived carbons (CDCs) in a wide range of applications is obstructed due to relatively high production costs. In this study a possibility to reduce the costs of CDC synthesis by employing low quality SiC byproducts stemming from the ESK process is presented. While the crystallinity and impurity content differs for the different precursor qualities, the resulting CDC materials possess similar textural characteristics and carbon microstructures. Evaluation of intrinsic kinetic data reveals that the low grade precursors react faster during reactive extraction and can be best described by a power law approach. The CDC materials were further investigated with respect to their performance as electrode materials in Electric Double Layer Capacitors (EDLC). All SiC-CDCs display a comparable and excellent specific capacitance of approx. 115Fg-1. The results are demonstrating the promising utilization of CDC materials synthesized from low valuable SiC feedstock.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; ESK process; Kinetic study; Reactive extraction

Size-controlled PtNi nanoparticles as highly efficient catalyst for hydrodechlorination reactions - Munoz, Macarena; Ponce, Sebastian; Zhang, Guirong; Etzold, Bastian (Applied Catalysis B-Environmental, 2016)
The application of size-controlled PtNi nanoparticles (NPs) as catalyst on the aqueous-phase hydrodechlorination (HDC) of 4-chlorophenol (4-CP) under ambient conditions (25 °C, 1 atm) has been investigated. NPs were synthesized as a co-reduction of both metals following a solvothermal method which allowed a proper control of the PtNi alloyed NP size in the range of 4.4–12.0 nm. To make the active sites of the nanoalloy accessible, the stabilizer poly(N-vinyl-2-pyrrolidone) was removed by washing of the NPs with H2O2/H2SO4. Evaluating the NP structure/composition influence on the activity, a clear synergic effect between Pt and Ni was found. In this sense, complete conversion of 4-CP was achieved in 1 h reaction time with the bimetallic NPs whereas only 70% was reached with the monometallic Pt counterpart (NP size = 12 nm, [Pt] = 80 mg L-1, [4-CP]0 = 78 extgreekmmol L-1). That effect could be related to the higher resistance of PtNi nanoalloy against chlorine poisoning compared to the monometallic Pt. In fact, PtNi NPs showed a remarkable stability and negligible deactivation even after storing the catalyst one month in the reaction mixture, whereas for the monometallic Pt fully deactivation resulted. The structure-sensitivity of HDC with PtNi nanocatalysts was finally confirmed as the catalytic performance was clearly dependent on the size. A volcano plot like behaviour was obtained, being 5.5 nm the optimum size. PtNi-5.5 led to the complete conversion of 4-CP in 15 min at a HDC rate of 3.12 L min-1 gPt-1.
EAM Import::2019-03-13

Synthesis of carbon core–shell pore structures and their performance as supercapacitors - Ariyanto, Ariyanto; Dyatkin, Boris; Zhang, Guirong; Kern, Andreas; Gogotsi, Yury; Etzold, Bastian (Microporous and Mesoporous Materials, 2015)
High-power supercapacitors require excellent electrolyte mobility within the pore network and high electrical conductivity for maximum capacitance and efficiency. Achieving high power typically requires sacrificing energy densities, as the latter demands a high specific surface area and narrow porosity that impedes ion transport. We present a novel solution for this optimization problem: a nanostructured core-shell carbonaceous material that exhibits a microporous carbon core surrounded by a mesoporous, graphitic shell. Our tunable synthesis parameters yielded a structure that features either a sharp or a gradual transition between the core and shell sections. Electrochemical supercapacitor testing using organic electrolyte revealed that these novel core-shell materials outperform carbons with homogeneous pore structures. The hybrid core-shell materials showed a combination of good capacitance retention, typical for the carbon present in the shell and high specific capacitance, typical for the core material. These materials achieved power densities in excess of 40 kW kg-1 at energy densities reaching 27 Wh kg-1.
EAM Import::2019-03-12